Occupational injuries identified by an emergency department based injury surveillance system in Nicaragua. Issue 4 (16th August 2004) - Noe, R; Rocha, J; Clavel-Arcas, C; Aleman, C; Gonzales, M E; Mock, C
Abstract : Objectives: To identify and describe the work related injuries in both the formal and informal work sectors captured in an emergency department based injury surveillance system in Managua, Nicaragua. Setting: Urban emergency department in Managua, Nicaragua serving 200–300 patients per day. Methods: Secondary analysis from the surveillance system data. All cases indicating an injury while working and seen for treatment at the emergency department between 1 August 2001 and 31 July 2002 were included. There was no exclusion based on place of occurrence (home, work, school), age, or gender. Results: There were 3801 work related injuries identified which accounted for 18.6% of the total 20 425 injures captured by the surveillance system. Twenty seven work related fatalities were recorded, compared with the 1998 International Labor Organization statistic of 25 occupational fatalities for all of Nicaragua. Injuries occurring outside of a formal work location accounted for more than 60% of the work related injuries. Almost half of these occurred at home, while 19% occurred on the street. The leading mechanisms for work related injuries were falls (30%), blunt objects (28%), and stabs/cuts (23%). Falls were by far the most severe mechanism in the study, causing 37% of the work related deaths and more than half of the fractures. Conclusions: Occupational injuries are grossly underreported in Nicaragua. This study demonstrated that an emergency department can be a data source for work related injuries in developing countries because it captures both the formal and informal workforce injuries. Fall prevention initiatives could significantly reduce the magnitude and severity of occupational injuries in Managua, Nicaragua.